H33: A Wheat Gene Providing Hessian Fly Resistance for the Southeastern United States. Issue 5 (1st September 2014) - McDonald, Melissa J.; Ohm, Herbert W.; Rinehart, Kristen D.; Giovanini, Marcelo P.; Williams, Christie E.
ABSTRACT: Hessian fly populations adapt to overcome newly deployed resistance genes within a few years of release. Although more than 34 genes have been identified that confer resistance against Hessian fly [ Mayetiola destructor (Say)] attack in wheat ( Triticum aestivum L.), only five genes currently provide resistance against fly populations in the southeastern United States. But even these genes are not 100% effective, leaving Georgia and North and South Carolina with between one and three effective genes for cultivar development. With the goal of providing much needed resistance for this region in a wheat line suitable for use with marker‐assisted selection, we identified a durum wheat line that confers resistance to Hessian fly populations from Maryland, Delaware, North and South Carolina, and Georgia in 100% of the plants tested. Resistance from this tetraploid durum line, PI 134942, was introgressed into hexaploid common wheat to generate the line 97211. Segregating populations of F2:3 families were constructed with the durum donor and with the common wheat recipient to identify resistance genes and provide flanking markers. Although the resistance of the durum donor appeared to involve more than one gene, one partially dominant but very effective gene, H33, was successfully transferred and identified in the hexaploid recipient. This gene was mapped to the short arm of wheat chromosome 3A and is flanked by single sequence repeat markers xgwm218 and hbg284.